Detection of alpha-synuclein aggregates in gastrointestinal biopsies by protein misfolding cyclic amplification - Fenyi, Alexis; Leclair-Visonneau, Laurène; Clairembault, Thomas; Coron, Emmanuel; Neunlist, Michel; Melki, Ronald; Derkinderen, Pascal; Bousset, Luc (Neurobiology of disease, 2019)
Lewy bodies and neurites, the pathological signatures found in the central nervous system of Parkinson's disease (PD) patients, are primarily composed of aggregated alpha-synuclein (aSyn). The observation that aSyn aggregates are also found in the enteric nervous system has prompted several studies aimed at developing a diagnostic procedure based on the detection of pathological aSyn in gastrointestinal (GI) biopsies. The existing studies, which have all used immunohistochemistry for the detection of pathological aSyn, have had conflicting results. In the current survey, we analyzed the seeding propensity of aSyn aggregates from GI biopsies. A total of 29 subjects participated to this study, 18 PD patients and 11 controls. For each patient, 2 to 4 GI biopsies were taken from the same site (antrum, sigmoid colon or rectum) and used to seed the aggregation of recombinant aSyn in an assay inspired from the protein misfolding cyclic amplification (PMCA) method. In a subset of patients and controls (14 and 3, respectively), one or two additional biopsies were analyzed by immunohistochemistry for the presence of phosphorylated aSyn histopathology (PASH) using antibodies against phosphorylated aSyn and PGP 9.5. Except for one subject, none of the control samples seeded aSyn aggregation in PMCA reaction. GI biopsies from patients with PD seeded aSyn aggregation in 10 out of 18 cases (7 from the sigmoid colon, 2 from the antrum and one from the rectum). There was good agreement between PMCA and immunohistochemistry results as, except for two cases, all PMCA-positive PD patients were also PASH-positive. Our findings show that the PMCA method we implemented is capable of detecting aSyn aggregates in routine GI biopsies. They also suggest that rectum biopsies do not contain sufficient amounts of aggregated aSyn to detect seeded assembly by PMCA. While encouraging, our findings indicate that further studies are needed to establish the diagnostic potential of the PMCA method we implemented to detect aSyn aggregates in upper GI biopsies. •Protein Misfolding Cyclic Amplification (PMCA) method to assess PD in GI biopsies.•GI biopsies seed aSYN aggregation in PMCA reaction.•10 out of 18 PD cases were found positive by PMCA, only 1 out of 11 controls.•Antrum or sigmoid colon biopsies are the most suited for PMCA-based PD diagnosis.